2019
DOI: 10.3892/or.2019.7284
|View full text |Cite
|
Sign up to set email alerts
|

EMX2 is epigenetically silenced and suppresses epithelial‑mesenchymal transition in human esophageal adenocarcinoma

Abstract: Esophageal adenocarcinoma (EAC) is an aggressive and challenging disease to treat, with an overall five-year survival rate of <20%. Early malignant cell dissemination contributes to this poor prognosis. Epithelial-mesenchymal transition (EMT) induces the invasion and metastasis of carcinoma cells. Empty spiracles homeobox 2 (EMX2) is a homeodomain-containing transcription factor, which is associated with numerous cancer types, and has been demonstrated to regulate EMT. In the present study, 48 pairs of EAC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…EMX2 has been shown to inhibit a number of cancer-related pathways, including PI3K/AKT [ 52 ] and Wnt/-catenin [ 53 ]. The Wnt/-catenin pathway is important for normal tissue morphogenesis as well as tumor development, including cervical cancer [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMX2 has been shown to inhibit a number of cancer-related pathways, including PI3K/AKT [ 52 ] and Wnt/-catenin [ 53 ]. The Wnt/-catenin pathway is important for normal tissue morphogenesis as well as tumor development, including cervical cancer [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMX2 has been shown to inhibit a number of cancerrelated pathways, including PI3K/AKT [52] and Wnt/catenin [53].…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with the results of a previous study which demonstrated that overexpressing EMX2 inhibits cell migration and invasion via suppressing Akt phosphorylation in esophageal adenocarcinoma cell lines. 29 As previous studies have shown activated Akt regulates the activity and expression of FOXO3a by binding to FOXO3a and regulating its phosphorylation. 15,[30][31][32] We then explored and found that EMX2 can bind with both Akt and FOXO3a.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, we found that high methylation silencing of cg14845689 in EXM2 could increase patient's prognostic risk. EXM2 is thought as a tumor suppressor gene, and high expression of EXM2 can induce cell cycle stagnation thereby inhibiting the proliferation of cancer cells [ 46 , 47 ]. SDK1 is a kind of immune-related protein, and studies found that SDK1 mutation causes cancers, but the effect of SDK1-related site methylation on the incidence of cancer has not been fully studied [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%